MANAJEMEN STRES MAHASISWA TINGKAT AKHIR DALAM PENYELESAIAN TUGAS AKHIR DI JURUSAN MANAJEMEN PENDIDIKAN ISLAM UIN ALAUDDIN MAKASSAR - Muzizah, Dian; Anwar HM, Muh.; Damayanti, Eka; Mardhiah; Ahmad Afiif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze stress management among final-year students in completing their undergraduate thesis at the Department of Islamic Educational Management, Faculty of Tarbiyah and Teacher Training, Alauddin State Islamic University of Makassar. This research employed a qualitative approach with a phenomenological design. The participants consisted of ten final-year students selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings revealed that the impacts of stress experienced by students include psychological, cognitive, physical, and behavioral aspects. The factors contributing to stress comprise cognitive appraisal of stressors, emotional regulation, personal resources, social support, self-acceptance, and coping strategies. To cope with stress, students applied various stress management strategies, including confrontative coping, seeking social support, planful problem solving, self-control, distancing, positive reappraisal, accepting responsibility, and escape/avoidance. Most participants tended to employ adaptive coping strategies that helped reduce stress levels and maintain motivation during the completion of their thesis. The study concludes that effective stress management is supported not only by students' personal coping abilities but also by academic and social support from supervisors, study programs, and educational institutions.